2019
DOI: 10.1002/mp.13331
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous cosegmentation of tumors in PETCT images using deep fully convolutional networks

Abstract: Purpose To investigate the use and efficiency of 3‐D deep learning, fully convolutional networks (DFCN) for simultaneous tumor cosegmentation on dual‐modality nonsmall cell lung cancer (NSCLC) and positron emission tomography (PET)‐computed tomography (CT) images. Methods We used DFCN cosegmentation for NSCLC tumors in PET‐CT images, considering both the CT and PET information. The proposed DFCN‐based cosegmentation method consists of two coupled three‐dimensional (3D)‐UNets with an encoder‐decoder architectur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 65 publications
0
56
0
1
Order By: Relevance
“…Zhao et al showed, for a small group of 30 patients, that the automatic segmentation of such tumors on 18 F-FDG PET/CT data was, in principle, possible using the U-Net architecture (mean Dice score of 87.47%) (44). Other groups applied similar approaches to head and neck cancer (45) and lung cancer (46,47). Still, fully automated tumor segmentation remains a challenge, probably because of the extremely diverse appearance of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al showed, for a small group of 30 patients, that the automatic segmentation of such tumors on 18 F-FDG PET/CT data was, in principle, possible using the U-Net architecture (mean Dice score of 87.47%) (44). Other groups applied similar approaches to head and neck cancer (45) and lung cancer (46,47). Still, fully automated tumor segmentation remains a challenge, probably because of the extremely diverse appearance of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…DL has been especially successful in medical image segmentation tasks (7), as the learning process occurs on the voxel level and not on the entire-image level (as for classification tasks), thereby reducing the requirements regarding the amount of learning data needed for efficient training. Recently, convolutional neural network approaches were applied to PET (50) and PET/CT segmentation (53)(54)(55). DL algorithms for PET tumor detection and segmentation (56) may provide fully automated solutions for these steps of the radiomics pipeline.…”
Section: Segmentationmentioning
confidence: 99%
“…Andrearczyk et al [5] expanded this work by investigating several segmentation strategies based on V-Net architecture on a publicly available dataset with 202 patients. Zhao et al [10] employed a multi-modality fully convolutional network (FCN) for tumor co-segmentation in PET-CT images on a clinic dataset of 84 patients with lung cancer, and Zhong et al [11] proposed a segmentation method that consists of two coupled 3D U-Nets for simultaneously co-segmenting tumors in PET/CT images for 60 non-small cell lung cancer (NSCLC) patients.…”
Section: Related Workmentioning
confidence: 99%